IMPLEMENTASI GERAKAN LITERASI SEKOLAH UNTUK MENINGKATKAN HASIL BELAJAR KELAS III SD PADA MATA PELAJARAN BAHASA INDONESIA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low motivation and interest in reading among students, which impacts their Indonesian language learning outcomes, particularly the class average score that has not yet reached completion. The main problem studied is the implementation of the School Literacy Movement (GLS) program at the habituation stage in improving the Indonesian language learning outcomes of third-grade students of Mojoagung 01 Elementary School, Pati Regency, and how the students' learning outcomes are after the program is implemented. The purpose of this study is to determine the implementation of GLS and its effect on improving student learning outcomes. This study uses a quantitative approach with an experimental method of one group pretest-posttest design. The study population is all third-grade students with a sample size of 21 children using a saturated sampling technique. Primary data were obtained through observation results, interview results, questionnaire results, pre-test and post-test results, while secondary data were obtained through teaching modules, and documentation. Primary data sources in this study were the principal, third-grade teachers, and third-grade students of Mojoagung 01 Elementary School, Pati Regency, while secondary data sources in this study were through journals, theses, books, and articles. Data collection techniques in this study were through interviews, questionnaires, observations, and tests. Data analysis in this study was through data normality tests, validity tests, reliability tests, and hypothesis tests using paired sample t-tests. The theoretical basis used includes the concepts of school literacy, learning outcomes, and Indonesian language learning and is strengthened by relevant research. The results of the study showed an average pretest score of 52.86 increased to 84.52 in the posttest with a mean difference of -31.66. A significance value of 0.000 <0.05 proves a significant difference between learning outcomes before and after the implementation of GLS. Thus, it can be concluded that the school literacy movement has a positive effect on improving the Indonesian language learning outcomes of third-grade students.